Electroplating in the modern era, improvements and challenges: A review - Emmanuel Chukwuebuka Gugua; Chika Oliver Ujah; Christian O. Asadu; Daramy Vandi Von Kallon; Benjamin Nnamdi Ekwueme (Hybrid Advances)
Electroplating has been a popular and valuable process in human civilisation since its discovery and gained widespread application in various areas, ranging from household to commercial/industrial. Hence, this work presents a systematic review of electroplating in the modern era, considering various stages of advancement and citing possible areas of improvement and the different challenges encountered. An overview of the electroplating concept is illustrated in the first section, followed by a deep dive into the prehistorical development of electroplating from ancient times, and how it became a commercial phenomenon. Also, it examined what prompted the need for further innovations and the innovations of recent times. Furthermore, the various techniques and kinds of materials used in the electroplating process were studied; the contributions to shaping man's activities; factors that hindered its progress; and steps taken to modernise its practices to meet sustainable best practices. As a way of conclusion, necessary recommendations were documented for further research goals for the furtherance of the technology, as it has proven its relevance over time.